PENGARUH PARENTAL HOLDING TERHADAP DISTRESS ANAK SELAMA PROSEDUR PEMASANGAN INFUS DI RUANG ANAK RUMAH SAKIT PEKANBARU MEDICAL CENTER - Nanda Wilda Lestari; Imron Rosyadi (Ensiklopedia of Journal, 2023)
The hospitalization process for children can cause psychological problems that interfere with children's growth and development, one of which is the occurrence of distress. One of the efforts that can be done to reduce child distress is to do parental holding, especially during the infusion procedure. The purpose of this study was to determine the effect of parental holding on child distress during the infusion procedure in the children's room of Tengku Rafian Hospital. The design of this study is a quasy experiment with one group pretest-posttest design. This research was conducted in the children's room of Tengku Rafian Hospital with a population of 24 people. The sampling technique uses a total sampling of 24 people with inclusion criteria: the patient is accompanied by biological parents during treatment, and is aged 6-12 years. Exclusion criteria: a child who does not experience limitations in moving the limbs.  The data collection tool in this study used the CFS instrument and the Pediatric Behavior Rating Scale and the results of the study were processed using the Pired Sample t-test. The results in this study found that there was parental holding of child distress during the infusion installation procedure in the children's room of Tengku Rafian Hospital (p-value = 0.000). The suggestion of this study is to create a medium of information about the benefits of parental holding during the process of treating children in hospitalsKeywords: Parental Holding, Child Distress, Infusion Installation.